2015
DOI: 10.1186/s12284-015-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Laser microdissection-based gene expression analysis in the aleurone layer and starchy endosperm of developing rice caryopses in the early storage phase

Abstract: BackgroundRice endosperm is composed of aleurone cells in the outermost layers and starchy endosperm cells in the inner part. The aleurone layer accumulates lipids, whereas starchy endosperm mainly accumulates starch. During the ripening stage, the starch accumulation rate is known to be asynchronous, depending on the position of the starchy endosperm. Different physiological and molecular mechanisms are hypothesized to underlie the qualitative and quantitative differences in storage products among developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…In rice, it is reported that the aleurone layer plays a pivotal role in apoplastic uptake of nutrition into the starchy endosperm (Bai et al ., ; Xu et al ., ; Ma et al ., ; Yang et al ., ). Compared with the starchy endosperm cells which have near‐zero oxygen concentration and few mitochondria, the aleurone layer cells have high oxygen concentrations (8%) and develop numerous mitochondria (Ishimaru et al ., ). The flo10 mutant develops abnormal aleurone, most probably resulting from the dysfunctional mitochondria (Figs c, ).…”
Section: Discussionmentioning
confidence: 97%
“…In rice, it is reported that the aleurone layer plays a pivotal role in apoplastic uptake of nutrition into the starchy endosperm (Bai et al ., ; Xu et al ., ; Ma et al ., ; Yang et al ., ). Compared with the starchy endosperm cells which have near‐zero oxygen concentration and few mitochondria, the aleurone layer cells have high oxygen concentrations (8%) and develop numerous mitochondria (Ishimaru et al ., ). The flo10 mutant develops abnormal aleurone, most probably resulting from the dysfunctional mitochondria (Figs c, ).…”
Section: Discussionmentioning
confidence: 97%
“…A fully developed endosperm, which occupies most of the seed space, has accumulated large amounts of storage substances. The endosperm consists of an outer aleurone layer (AL) inside which is the starchy endosperm (SE) (Becraft, 2001; Krishnan and Dayanandan, 2003; Zuo and Li, 2014; Ishimaru et al , 2015; Wu et al , 2016). Proteins, lipids, and minerals are accumulated in the AL, whereas starch and small amounts of storage proteins are mainly stored in the SE (Olsen, 2004; Zheng and Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For validating the spatial and temporal expression patterns and further exploring the specific expression distribution of ONAC127 and ONAC129 in caryopsis, we mechanically isolated rice caryopses at 5-14 DAP to the mixture of pericarp and aleurone layer, starch endosperm and embryo for qRT-PCR analyses by the method described by Bai (Bai et al, 2016). The aleurone layer specifically expressed gene oleosin and the starch endosperm specifically expressed gene SDBE were used as markers (Ishimaru et al, 2015) (Supplemental Fig. S1).…”
Section: Resultsmentioning
confidence: 99%